2014
DOI: 10.1186/2251-6581-13-31
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive status and foot self care practice in overweight diabetics, engaged in different levels of physical activity

Abstract: BackgroundType 2 diabetes along with chronic hyperglycemia may result in cognitive impairment. This can negatively affect the patient’s adherence to diabetes treatment. The purpose of this study was to compare the cognitive status and foot self care practice in overweight type 2 diabetic patients who exercised regularly and those who did not.MethodsThe comparative study was conducted on 160 consecutive patients from an outpatient diabetes clinic. They were divided into two groups: The active group comprised of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
(65 reference statements)
0
4
1
Order By: Relevance
“…In addition, the direction of the correlation between the Mini-MoCA orientation and physical activity was the reverse of what was initially hypothesized. Unlike the current study results, evidence has shown a positive association between cognitive function and physical activity in older adults with T2D (Feil et al, 2012; Madarshahian et al, 2014). The reversed findings observed in this study may be attributable to the homogeneous characteristics of the sample.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the direction of the correlation between the Mini-MoCA orientation and physical activity was the reverse of what was initially hypothesized. Unlike the current study results, evidence has shown a positive association between cognitive function and physical activity in older adults with T2D (Feil et al, 2012; Madarshahian et al, 2014). The reversed findings observed in this study may be attributable to the homogeneous characteristics of the sample.…”
Section: Discussioncontrasting
confidence: 99%
“…Our choice of study variables was based on similar studies that examined the relationship between DFD (or diabetes) and other factors [19][20][21][22][34][35][36][37][38][39][40]. For instance, the study by included age, sex, socioeconomic status, education level, smoking status and depression while investigating the associated factors of foot complications in a representative inpatient population of Australia [20].…”
Section: Study Variablesmentioning
confidence: 99%
“…With regards to the health care providers progression and their role, Shokoohi et al, showed that residents of Internal Medicine as Educational Influentials (EIs) in clinical settings, play a key role in knowledge transfer [11]. Moreover, considering continuous education about foot self-care practice is necessary for patients with DM, a study with the aim of comparing the cognitive status and foot self-care practice in overweight patients with type 2 diabetes, conducted and the result showed that regular physical activity could promote the cognitive status and foot self-care practice [12].…”
Section: Df Prevention Classification and Risk Stratificationmentioning
confidence: 99%